The Advances in Joining Technology - Awang, Mokhtar (Lecture Notes in Mechanical Engineering, 2019)
This volume presents selected papers from the 3rd International Conference on Mechanical, Manufacturing and Process Plant Engineering (ICMMPE 2017) which was in Penang, Malaysia, 22nd-23rd November 2017. The proceedings discuss genuine problems covering various topics of mechanical, manufacturing, and Process Plant engineering.